Psychosocial Problems Faced by Nurses in Caring for Patients with COVID 19: A Phenomenology Study - Jenny Marlindawani Purba; Sri Eka Wahyuni; Mahnum Lailan Nasution; Wardiyah Daulay (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2021)
Introduction: The high prevalence of exposure to corona virus among health workers has a psychosocial impact on nurses in charge of isolation wards specifically for COVID-19 patients. Therefore, this study aims to explore the psychosocial problems faced by nurses in the isolation wards of COVID-19 patients at the referral hospital in Medan.Methods: A qualitative study design with a phenomenological approach was used, and participants were selected using a purposive sampling technique. Data was obtained from 10 of these participants working in isolation wards and providing direct care to patients infected with corona virus. This was carried out through an in-depth face-to-face interview using internet facilities and the data was analyzed using colaizzi method.Results: The result showed that caring for patients confirmed with COVID-19 is a new challenge for nurses and the increase in the number of patients and health workers exposed to the virus had a psychosocial impact on them. Therefore, three themes were produced in this study, namely: (1) feeling of anxiety (2) feeling uncomfortable (3) boredom and fatigue.Conclusion: It was discovered that treating patients confirmed with COVID-19 has a psychosocial impact on nurses in isolation rooms. Therefore, this impact in nurses should be a major concern to help them cope with psychosocial problems, which will enable them provide professional nursing care to patients with COVID-19.